Grasshopper pie and other poems - Steinberg, David, 1962-; Sinnott, Adrian C. (New York : Grosset & Dunlap, 2004)
Five poems celebrate the making of a very special pie, an upside-down boy, a sneezing elephant, an encounter with a monster, and an alien who lands in a bowl of chicken soup.
Grasshopper pie -- The legend of Billy Ray Brown -- Louise's sneezes -- The Tickle Monster -- An alien in my soup.
School Library Journal, October 2004.
Booklist, July 2004.
Horn Book, April 2005.
School Library Journal.
Booklist.
Horn Book.
Keywords: Children's poetry, American; Humorous poetry; American poetry; Humorous poetry; American poetry; Humorous poetry; American poetry; Readers (Elementary)